1834. Implementation of the Core Elements of Outpatient Antibiotic Stewardship in Urgent Care Centers and Federally Qualified Health Centers in New York City, 2016–2017. (26th November 2018) - Foote, Mary; Airall-Simon, Gloria; Oriuwa, Christian; Kellner, Pamela
Abstract: Background: Studies suggest that 80% of antibiotics are prescribed in the outpatient setting and at least 30% of these prescriptions are unnecessary. In 2016, the CDC released the Core Elements of Outpatient Antibiotic Stewardship to provide a framework for outpatient facilities to reduce unnecessary antibiotic prescribing; but little is known regarding their implementation across various outpatient settings. Methods: The NYC Department of Health and Mental Hygiene conducted voluntary on-site infection control assessments at 29 outpatient clinics in New York City in 2016–2017. Participants completed an 18-item questionnaire based on the facility checklist for the Core Elements of Outpatient Antibiotic Stewardship to assess implementation of the four core elements (CE), including (1) commitment, (2) action, (3) tracking and reporting, and (4) education and expertise (EE). Descriptive statistics summarized facility characteristics and frequency of reported interventions. Results: Seventeen Federally Qualified Health Centers (FQHC) and 12 Urgent Care Centers (UCC) completed the questionnaire. All FQHCs had infection control (IC) policies and procedures vs. 75% of UCCs. Overall, 14 (48%) could demonstrate commitment; 16 (55%) implemented an action to improve antibiotic prescribing; 10 (34%) track and report on antibiotic prescribing; 15 (52%) provide EE to prescribers; 7 (24%) reported having all four CE in place. More facilities with a competency-based infection control training program or a designated stewardship leader had all four CEs in place compared with those that did not (86% vs. 14% and 71% vs. 29%, respectively). Conclusion: Though this sample represents only a small portion of these facility types in NYC, this is the first effort to assess stewardship practices in UCCs and FQHCs to our knowledge. We found that designating a stewardship leader appears to be an important step to implementing the CE. However, given that only a quarter of facilities had implemented all four elements, there is a clear need to further assess stewardship activities in the various outpatient settings to better understand the gaps and barriers to implementation. Disclosures: All authors: No reported disclosures.